Investigating the Role of Earthquakes on the Stability of Dangerous Rock Masses and Rockfall Dynamics - Zheng, Lu; Wu, Yihan; Zhu, Zhiyuan; Ren, Kaihui; Wei, Qi; Wu, Wei; Zhang, Hong (Frontiers in Earth Science, 2022)
In recent years, earthquake rockfalls have occurred frequently all over the world, resulting in heavy casualties and property losses. Unfortunately, research on rockfall dynamics upon earthquake events is still rare due to limited field and experimental data, and restricted to numerical simulations of only two dimensions. In order to primarily reveal the role of earthquakes on rockfall, this study focused on the stability of rock blocks on an inclined slope, and following rockfall dynamics by three-dimensional discontinuous deformation analysis (3-D DDA). First, earthquake input methods were discussed and implemented for the triangulated regular network (TRN) in 3-D DDA. The effectiveness was verified by comparison with analytical solution results of a single block on the inclined slope under seismic loads. Further, by discussing the variations of the boundary chart of failure modes, it indicated that the block was more prone to slide even with a large friction angle, became instability under seismic conditions. Moreover, a regular dodecahedron rock block was released on a stochastic roughness slope with two platforms through parallel realizations. The indices of the movement characteristics of the block, such as runout distance, lateral displacement range, and resting position, were investigated. The results showed that the maximum runout distance was not sensitive to seismic load, but the lateral displacement range was significantly sensitive to seismic load and increased appreciably. Through the 3D-DDA numerical simulations, both rock stability and rockfall behaviors under earthquake conditions could be better understood. Furthermore, it will be helpful to by analyzing trajectories and kinetic energies predict earthquake rockfall disasters and design reasonable protective countermeasures under earthquake scenarios.